APPLYING THE PRESUMPTION OF INNOCENCE PRINCIPLE AGAINST SHOOTING ON-SIGHT BY THE POLICE IN POSO REGENCY - Kaharuddin Syah; Samsuria Samsuria (Fakultas Hukum Universitas Muhammadiyah Palu, 2021)
The Presumption of innocent principle is one of the principles regulated in criminal procedural law which in general explanation number 3 letter c the Presumption of innocent principle in its implementation is often clashed with a policy of shooting on sight as happened in the case of shooting at the victim's place named Qidam Alfariski Mofance, a resident of the village, Tambarana, Poso Regency, Central Sulawesi Province. The problem that will be discussed in this paper is how to apply this principle to the act of shooting on sight by the Police in the perspective of law enforcement and accountability. The method in this research is empirical normative juridical. Sources and types of data used are primary, secondary and tertiary data. Based on the results of the author's research, it can be seen that the application of the Persumption of innocence principleagainst the shooting on sight to Qidam Alfariski Mofance is an act of violation of law and human rights if the intent of the crime is not known